2021
DOI: 10.3390/biology10111074
|View full text |Cite
|
Sign up to set email alerts
|

Deficiencies in Root Canal Fillings Subsequent to Adaptive Instrumentation of Oval Canals

Abstract: The purpose of this study was to explore the influence of instrumentation and the potential for debris deposition using XP-endo shaper plus (XP-SP) and full-sequence SAF (F-SAF) on the adaption of thermoplastic root canal fillings in oval canals. Following the manufacturer’s instructions, ninety human permanent mandibular incisors with a single oval canal 6 mm from the apex (verified using pre-operative CBCT scanning) were instrumented with XP-SP and F-SAF. Obtura III Max apparatus was used for root canal obtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Recently, other new types of instruments were introduced, which were specially designed to address the shaping and cleaning of oval canals, such as the XP-endo shaper and XP-endo finisher [ 26 , 27 , 28 , 29 , 30 ]. It will be of interest to test the effect of these instruments on the bond strength of root canal fillings in oval canals, nevertheless, such comparison was beyond the scope of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, other new types of instruments were introduced, which were specially designed to address the shaping and cleaning of oval canals, such as the XP-endo shaper and XP-endo finisher [ 26 , 27 , 28 , 29 , 30 ]. It will be of interest to test the effect of these instruments on the bond strength of root canal fillings in oval canals, nevertheless, such comparison was beyond the scope of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This is because traditional rotary instrumentation usually prepares a round cross-sectional shape, which results in disproportionate dentin removal, with some regions receiving considerable dentin removal while others receive none. Research has indicated that the effectiveness of irrigation strategies in oval-shaped canals can differ based on the irrigant type, irrigation volume and pressure, and activation methodology [18][19][20]. Considering oval root canals have a larger surface area and a more irregular form, which might alter the flow and distribution of irrigation solutions, using oval-shaped teeth in a study on irrigation techniques is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Considering oval root canals have a larger surface area and a more irregular form, which might alter the flow and distribution of irrigation solutions, using oval-shaped teeth in a study on irrigation techniques is crucial. A better understanding can be gained of how well various irrigation strategies work to remove pathogens, debris, and necrotic tissue from difficult canals by using oval-shaped teeth in studies [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%